2005
DOI: 10.1158/1078-0432.ccr-04-2000
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Cytokines Correlated with Altered Behavior, Serum Cortisol Rhythm, and Dampened 24-Hour Rest-Activity Patterns in Patients with Metastatic Colorectal Cancer

Abstract: Purpose: Incapacitating symptom burden in cancer patients contributes to poor quality of life (QOL) and can influence treatment outcomes because of poor tolerance to therapy. In this study, the role of circulating cytokines in the production symptoms in cancer patients is evaluated.Experimental Design: Eighty patients with metastatic colorectal cancer with either normal (group I, n = 40) or dampened (group II, n = 40) 24-hour rest/ /activity patterns measured by actigraphy were identified. Actigraphy patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
180
4
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 226 publications
(193 citation statements)
references
References 54 publications
6
180
4
3
Order By: Relevance
“…Significant correlations were found between serum levels of TGF-α and IL-6, circadian patterns in wrist activity, and serum cortisol and tumor-related symptoms in 80 patients with metastatic colorectal cancer. These data support clinically relevant links between tumor cytokines and the circadian timing system (Rich et al 2005;Rich 2007). …”
Section: A Hypothetical Model Of the Interactions Between Circadian Tsupporting
confidence: 60%
“…Significant correlations were found between serum levels of TGF-α and IL-6, circadian patterns in wrist activity, and serum cortisol and tumor-related symptoms in 80 patients with metastatic colorectal cancer. These data support clinically relevant links between tumor cytokines and the circadian timing system (Rich et al 2005;Rich 2007). …”
Section: A Hypothetical Model Of the Interactions Between Circadian Tsupporting
confidence: 60%
“…In our study also, chronoIFLO was also safe in older patients with a PS score <2. The activity and acceptable tolerability of chronoIFLO could relate to persistent circadian physiology in MCRC patients with a good PS score, as revealed by strong 24-hour rhythms in rest/activity and plasma cortisol in these patients [33,38,39]. Conversely, ablated circadian physiology constituted a poor prognostic factor for patients with metastatic cancer from colorectal as well as breast origin [33,[38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…The activity and acceptable tolerability of chronoIFLO could relate to persistent circadian physiology in MCRC patients with a good PS score, as revealed by strong 24-hour rhythms in rest/activity and plasma cortisol in these patients [33,38,39]. Conversely, ablated circadian physiology constituted a poor prognostic factor for patients with metastatic cancer from colorectal as well as breast origin [33,[38][39][40]. Similarly, tumors grew faster in rodent models with circadian physiology that had been ablated through clock gene mutation or environmental alterations [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have identified several ligands of interest, including TGF-a, prokinectin-2 (PK2; a molecule closely related to endocrine tissue VEGF), and cardiotropin-like cytokine (Clc; a molecule related to the proinflammatory cytokine interleukin 6). Although currently no clinical data support these associations in patients with RCC, clinical observations have linked elevated levels of TGF-a with fatigue, appetite loss, and flattened circadian rhythms in patients with metastatic colorectal cancer (17).…”
Section: Circadian Rhythm Disruptionmentioning
confidence: 99%